2011
DOI: 10.1093/ndt/gfr477
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal acute kidney injury in a tertiary center in a developing country

Abstract: The prevalence of newborn AKI in our Thai tertiary center over 24 years was 6.3% of admitted newborns. Sepsis was the most common cause of AKI and sepsis-induced AKI is the most common cause of death. Disease etiology was the only risk factor for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…However, renal function improved in the majority of patients by appropriate antibiotic therapy and supportive management, with no residual renal impairment, which is in accordance with previous reports (11,12). Similar to previous studies, AKI occurred more commonly in male than female neonates in our study, which is secondary to the increased incidence of septicemia and respiratory distress syndrome in male infants (8)(9)(10).…”
Section: Discussionsupporting
confidence: 92%
“…However, renal function improved in the majority of patients by appropriate antibiotic therapy and supportive management, with no residual renal impairment, which is in accordance with previous reports (11,12). Similar to previous studies, AKI occurred more commonly in male than female neonates in our study, which is secondary to the increased incidence of septicemia and respiratory distress syndrome in male infants (8)(9)(10).…”
Section: Discussionsupporting
confidence: 92%
“…These data correlate with the data described in several studies. [16][17] But we think that the incidence of neonatal AKI in our NICU is likely higher than it is reported in the present study. Namely, infants very often have non oliguric AKI.…”
Section: Discussioncontrasting
confidence: 64%
“…In a group of neonates with AS ≤ 6, Gupta et al (19) found that the incidence of AKI was 47% and mortality was 14.1%. Those findings were confirmed by similar results of other authors (1,23,24). Choker et al (25) found that neonates with AKI had significantly lower GS and BW than those without AKI.…”
Section: Discussionsupporting
confidence: 85%